HUBUNGAN USIA DAN PARITAS IBU DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD RADEN MATTAHER JAMBI - Silvia Mariana (STIKES Keluarga Bunda Jambi, 2019)
ABSTRACT Asphyxia is a condition of the newborn who does not immediately breathe spontaneously, the reproductive status of the mother also affects the incidence of asphyxia needed by mothers at risk and also at the risk of parity can cause complications or complications. The aim was to determine the relationship between age and parity of mothers with neonatorial asphyxia in Rsud Raden Mattaher Jambi. the method used is: Case-Control using a retrospective approach. With 3 variables, namely the independent variable is age, maternal parity and the dependent variable is neonatal asphyxia, analysis of data with univariate and bivariate analysis to determine the relationship of age and parity with the incidence of neonatal asphyxia using the chi square test. The results showed that the majority of mothers at risk of not having neonatal asphyxia (39.8%) and at risk of neonatal asphyxia (55.7%) meant that there was a relationship between age and neonatal asphyxia with P-Value 0.028 and OR 1,908 . And parity of mothers who are not at risk of not experiencing neonatal asphyxia (57.6%), parity is at risk of experiencing neonatal asphyxia (62.5%). There is a relationship between parity and neonatal asphyxia with P-Value 0.004 and OR 2.268. The conclusion is there is a relationship between age and parity of mothers with the incidence of neonatal asphyxia. Efforts can be made to provide counseling about the optimal age for pregnancy, encourage mothers to ANC at least 4 times and set a pregnancy distance of at least 3 years.